A new species of Dieffenbachia (Araceae) from Limón Province, Costa Rica. Issue 2 (3rd July 2017) - Ortiz, Orlando O.; Croat, Thomas B.
Abstract: Dieffenbachia rodriguezii, is described as a species new to science. It is known only from Limón Province at 1400 m, in a Lower montane rain forest life zone. Based on inflorescence morphology and leaf-blade shape, the new species is most similar to Dieffenbachia oerstedii Schott, Dieffenbachia grayumiana Croat and Dieffenbachia killipii Croat. The affinities of this species are discussed and a key for Costa Rican Dieffenbachia is provided.